FINANCIAL INSTITUTIONS AND THEIR ROLE IN THE DEVELOPMENT AND FINANCING OF SMALL INDIVIDUAL PROJECTS - Rawaa Ghazi Abdul wahid; Anmar Adnan Khudhair Al-Dulaimi; Mohammed Tareq Abdulwahhab (Scholar Express Journals, 2022)
Financial institutions are one of the most important components of any country's financial system. They play a vital role in determining the effectiveness and efficiency of the financial system , And comes in the importance of financial institutions in that they provide the economy services for richer than them, They represent the vital infrastructure through which money flows from savings to investors in various economic fields. Interest in medium and small enterprises is one of the factors of economic growth. Small and medium enterprises sector is an important sector of the national economy, Through its contribution to economic development, increasing domestic output ... etc. Small individual projects are of interest to different countries of the developed and developing world alike, Starting from the vital role of these projects in economic growth and job creation, And activating local and regional development. The aim of this research is to shed light on the experience of the Iraqi private banks listed in the Iraqi market for securities as one of the financial institutions that play a large role in providing the cash needed to develop and finance small individual projects
Keywords: Financial Institutions; Banks; Small Enterprises; financial